2021
DOI: 10.1002/ange.202102047
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Polymer Glasses with Lava and Healing Ability for High‐Performance Gas Sieving

Abstract: Coordination polymer (CP) glasses offer aw ay to tackle the fabrication challenges encountered by inorganic porous membranes and showgreat potentials for size-exclusive gas separation. However,their processability and performance still cannot simultaneously meet the requirements for highperformance membrane separation. Herein, we have developed aseries of CP glasses (M-P-dmbIm, M = Zn, Cd, Cu, and Mn), whichpossess low vitrification temperature as well as low viscosity (h)a nd lave capability above the transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…above their melting temperature, T m ) and vitrification to a MOF glass after cooling below their glass transition temperature (T g ) [21][22][23][24][25] . MOF glasses propose unique opportunities for solid-state ion conduction 20,26,27 and gas separation membranes [28][29][30] because of improved performance as a result of their monolithic structure and the absence of mass transport limiting grain boundaries 31 . However, compared to their structurally well-defined crystalline parent materials, it is very difficult to predict and design the functionally relevant porosity features (pore volume and pore size) of the MOF glasses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…above their melting temperature, T m ) and vitrification to a MOF glass after cooling below their glass transition temperature (T g ) [21][22][23][24][25] . MOF glasses propose unique opportunities for solid-state ion conduction 20,26,27 and gas separation membranes [28][29][30] because of improved performance as a result of their monolithic structure and the absence of mass transport limiting grain boundaries 31 . However, compared to their structurally well-defined crystalline parent materials, it is very difficult to predict and design the functionally relevant porosity features (pore volume and pore size) of the MOF glasses.…”
mentioning
confidence: 99%
“…ZIF-76, lta topology; ZIF-8, sod topology) [40][41][42] . Given that the crystalline ZIF precursors are typically microporous solids with porosity features interesting for gas storage and separation [43][44][45][46][47] , their melt-quenched glasses are deemed to exhibit similar potential for gas adsorption and separation processes 28,29 . Nevertheless, gas-accessible microporosity in MOF glasses has only been poorly investigated and was just demonstrated for a few ZIF glasses 30,37,38,48 .…”
mentioning
confidence: 99%
“…above their melting temperature, Tm) and vitrification to a MOF glass after cooling below their glass transition temperature (Tg). [21][22][23][24][25] MOF glasses propose unique opportunities for solid state ion conduction 20,26,27 and gas separation membranes [28][29][30] because of improved performance as a result of their monolithic structure and the absence of mass transport limiting grain boundaries. 31 However, compared to their structurally well-defined crystalline parent materials, it is extremely difficult to predict and design the functionally relevant porosity features (pore volume and pore size) of the MOF glasses.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] Given that the crystalline ZIF precursors are typically microporous solids with porosity features interesting for gas storage and separation, [43][44][45][46][47] their melt-quenched glasses are deemed to exhibit similar potential for gas adsorption and separation processes. 28,29 Nevertheless, gas-accessible microporosity in MOF glasses has been only poorly investigated and was just demonstrated for ZIF glasses obtained from ZIFs with cag topology. 30,37,38 A quantification of the total gas-accessible pore volume of the ZIF glasses as well as a comprehensive comparison of the porosity of the glasses in relation to their crystalline precursors has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that the in situ melting of ZIF-62 within the polyimide matrix was very effective in reducing meso- and macroscale defects at the MOF/polymer interface, resulting in a 23.7% increase in CO 2 /N 2 selectivity. Except for the a g ZIF-62 and a g (ZIF-62) 0.2 (6FDA-DAM) 0.8 membrane, other MOF glass membranes such as M-P-dmbIm 17 and TIF-4 membranes 18 also showed outstanding CO 2 separation performance.…”
mentioning
confidence: 99%